The effect of service quality and satisfaction on tourist customer loyalty in Slopeng Beach, Sumenep Regency - Nengsi, Nur Safika Nengsi; Andriani, Nurita (Institute of Computer Science (IOCS), 2023)
The purpose of the study was to determine the effect of service quality and satisfaction on customer loyalty. The purpose of this study is to determine how much influence the quality of service has on tourist satisfaction in Slopeng Beach, Sumenep Regency. To find out how much influence the quality of service has on tourist loyalty in Slopeng Beach, Sumenep Regency. To find out how much influence of tourist satisfaction on tourist loyalty in Slopeng Beach, Sumenep Regency. The population in this study is tourists who visit Slopeng Beach tourism Sumenep Regency. Sampling in this research was carried out using questionnaires using the purposive sampling method. The data analysis method used in this study is SEM (structural Equation Model) using SmartPLS